Correlation of VLF-EM Data with Radiometric Measurements: Implications for Uranium Exploration around Beldih, South Purulia Shear Zone, India. (27th March 2014) - Mittal, Saurabh; Sharma, S. P.; Biswas, Arkoprovo; Sengupta, D.
Abstract : This study is an attempt to correlate VLF-EM data with the radiometric measurements to decipher the subsurface structure and to locate uranium mineralization in the shear zone. The study area is around Beldih mine which is an open cast apatite mine located on the South Purulia Shear Zone. VLF method has been applied to map the structure and the presence of radioactive minerals has been delineated by the detection of high α and γ counts with respect to the background radiations. High radiation counts and high surface γ activity are found just above the higher apparent current-density zones in all the profiles studied, at various locations, indicating uranium and/or thorium mineralization as well as good correlation between these techniques.